Heat and Mass Transfer Enhancement of MHD Hybrid Nanofluid Flow in the Presence of Activation Energy - M. Shanmugapriya; R. Sundareswaran; P. Senthil Kumar (International Journal of Chemical Engineering)
In this study, water is apprehended as conventional fluid with the suspension of two types of hybrid nanoparticles, namely, single-walled CNTs (SWCNTs) and multiwalled CNTs (MWCNTs). The influence of a magnetic field, thermal radiation, and activation energy with binary chemical reaction has been added to better examine the fine point of hybrid nanofluid flow. The mathematical structure regarding the physical model for hybrid nanofluid is established and then the similarity variables are induced to transmute the leading PDEs into nonlinear ODEs. These equations were solved using the shooting technique together with RKF 4-5th order for various values of the governing parameters numerically. The results of prominent parameters were manifested through graphs and tables. The results indicate that the hybrid nanofluid SWCNT−MWCNT/water is fully adequate in cooling and heating compared to other hybrid nanofluids. In addition, the rise in the value of activation energy E upsurges the nanoparticle transfer rate of hybrid nanofluid.